2014
DOI: 10.1007/s00213-014-3733-9
|View full text |Cite
|
Sign up to set email alerts
|

Social stress and escalated drug self-administration in mice I. Alcohol and corticosterone

Abstract: Rationale Stress experiences have been shown to be a risk factor for alcohol abuse in humans; however, a reliable mouse model using episodic social stress has yet to be developed. Objectives The current studies investigated the effects of mild and moderate social defeat protocols on plasma corticosterone, voluntary alcohol drinking, and motivation to drink alcohol. Methods Outbred CFW mice were socially defeated for 10 days during which the intruder mouse underwent mild (15 bites: mean = 1.5 min), or moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 83 publications
(101 reference statements)
7
76
0
Order By: Relevance
“…For example, increased ethanol intake was observed several weeks after the experience of social defeat stress (Sillaber et al, 2002). A recent report indicated that mice subjected to a more intense regimen of social defeat show a significant decrease in ethanol intake during the days of stress experience but a significant increase in ethanol consumption the week immediately after the stress exposure was terminated (Norman et al, 2015). This ‘delayed’ or ‘rebound’ effect was not observed in the present experiment with any of the stress procedures examined.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased ethanol intake was observed several weeks after the experience of social defeat stress (Sillaber et al, 2002). A recent report indicated that mice subjected to a more intense regimen of social defeat show a significant decrease in ethanol intake during the days of stress experience but a significant increase in ethanol consumption the week immediately after the stress exposure was terminated (Norman et al, 2015). This ‘delayed’ or ‘rebound’ effect was not observed in the present experiment with any of the stress procedures examined.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to stressful life events can profoundly increase the vulnerability to psychostimulant and alcohol use in humans (Sinha 2001; Sinha 2008). Preclinical studies confirm that rats exposed to certain stressful events, such as mild foot shock, social defeat, or social isolation, self-administer increased amounts of cocaine and other drugs (Bossert et al 2013; Piazza and Le Moal 1998), and this link extends also to laboratory mice and alcohol consumption (Norman et al 2014 submitted). Understanding the underlying neurobiological mechanisms that link stress and drug intake is a critical first step in the development of effective treatments for stress-induced drug use disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of stress on drug use have been intensively investigated, few studies have considered the intensity and duration of the stressor (Norman et al 2014 submitted). The present study used Swiss Webster (CFW) mice as subjects since this outbred strain is characterized by substantial genetic and phenotypic variation, more similar to the human population than inbred strains.…”
Section: Introductionmentioning
confidence: 99%
“…Because patients enrolled in these studies also tend to have an extensive history of symptoms and medication use, it is challenging to reveal direct consequences of chronic psychosocial stress itself. In contrast, animal models allow investigation of specific stressors in a controlled manner to establish the mechanisms connecting chronic psychosocial stress exposure, brain activation, and subsequent emotional and social behaviour.Chronic social defeat stress (CSDS) is a rodent model of psychosocial stress, which produces many behavioural features similar to the symptoms of human anxiety and mood disorders, such as social aversion, anhedonia (decreased sucrose-preference) and increased self-administration of drugs of abuse 10,11 . These behavioural phenotypes last for several weeks post-stress 10 , and can be reversed by chronic treatment with selective serotonin re-uptake inhibitors or tricyclic antidepressants 12 , or a single dose of ketamine 13 .…”
mentioning
confidence: 99%